ΑΡΧΕΙΟ ΥΠΗΡΕΣΙΑΣ ΕΦΟΔΙΑΣΜΟΥ-ΔΙΑΝΟΜΩΝ (Α.Υ.Ε.Δ.) (1945-1948) - ΠΑΠΑΔΟΠΟΥΛΟΥ, ΚΑΤΕΡΙΝΑ; ΚΑΛΑΝΤΖΗΣ, ΓΙΩΡΓΟΣ (Μνήμων, 1991)
<span style="font-size: 10.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EL; mso-fareast-language: EL; mso-bidi-language: AR-SA;">Δεν παρατίθεται περίληψη.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->